Lysenko's ghost : epigenetics and Russia - Graham, Loren R. (Cambridge, Massachusetts : Harvard University Press, 2016)
"Epigenetics, a new field in biology, has shown that in some instances organisms can inherit characteristics acquired by their ancestors during their lifetimes, a view that was discredited during most of the twentieth century. Trofim Lysenko, a Russian agronomist long considered a charlatan, was a strong advocate of the inheritance of acquired characteristics. In the last few years a number of Russian science writers and scientists have claimed that epigenetics proves that Lysenko was right after all. This book evaluates that claim."--Provided by publisher.
The friendly siberian foxes -- The inheritance of acquired characteristics -- Paul Kammerer, enfant terrible of biology -- The great debate about human heredity in 1920s Russia -- Lysenko up close -- Lysenko¿s biological views -- Epigenetics -- The recent rebirth of Lysenkoism in Russia -- Surprising effects of the new Lysenkoism -- Anti-Lysenko Russian supporters of the inheritance of acquired characteristics.
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed March 30, 2016).
In English.
Master record variable field(s) change: 072
Keywords: Lysenko, Trofim, -- 1898-1976.; Lysenko, Trofim, -- 1898-1976.; Lysenko, T. D. -- 1898-1976; Lysenko, Trofim, -- 1898-1976.; Epigenetics -- Russia (Federation); SCIENCE -- Life Sciences -- Evolution; Epigenetics; Russia (Federation); Epigenetik; Russische SFSR; Epigenomics; Russia; SCIENCE / Life Sciences / Biology; Electronic books